Design of two–degree–of–freedom robust system for ground vehicle equipment stabilization - Sushchenko, Olha (Eastern-European Journal of Enterprise Technologies, 2016)
Features of design of the robust systems for stabilization of the moving platforms with equipment assigned for functioning at the ground vehicles are represented. The problem of design of the two–degree–of–freedom robust stabilization system taking into consideration coordinate disturbances and measurement noise is solved. To achieve this goal the optimization functional including the functions of sensitivity by the coordinate disturbances and the measurement noise was introduced. Taking into consideration the introduced functional the problem of the structural synthesis of the two–degree–of–freedom robust stabilization system is transformed to the standard Н∞–synthesis problem. The generalized plant model in the state space is obtained. This gives the possibility to use the automated tools of the researched problem solving by means of Robust Control Toolbox in the MatLab system. The approach to loop shaping with the desired frequency characteristics is implemented. With this aim the transfer functions of pre– and post–compensators are determined and the augmented plant is formed. Taking into consideration above stated concepts the basic phases of the structural synthesis procedure of the robust system for control by the angular motion of the platform with the observation equipment assigned for operation at the ground vehicles are given. The appropriate mathematical description of the plant in the state space is developed. The robust controller represented as quadruple of the state space matrices is obtained. Modelling results proving the possibility to provide the high system characteristics in difficult conditions of the real operation are represented. The influence of the coordinate disturbances such as the friction moment, unbalance moment, moments caused by irregularities of roads (the road with the long undulations) and terrain (the terrain with hummocks), by which the vehicle moves, is considered. Also the possibility to keep the ability of the system to operation in conditions of the parametric disturbances in the wide range for the changed plant inertia moment and the coefficient of the elastic connection between the actuator and the base, at which the plant (the platform with the observation equipment) is mounted, is shown.